Correlations of acidity-basicity of solvent treated layered double hydroxides/oxides and their CO2 capture performance. Issue 27 (24th June 2020) - Leung, D. W. Justin; Chen, Chunping; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Acid/basic properties of LDHs can be fine-tuned by using (AMO or AIM) solvent treatments. Furthermore, the CO2 adsorption per surface area increases with increasing acid/base ratio. Abstract : The basicity and acidity of solvent-treated layered double hydroxide (ST-LDHs) and their layered double oxides (ST-LDOs) have been fully studied using Hammett titration, in situ FTIR, CO2 -TPD and NH3 -TPD. Five solvents (ethanol, acetone, isopropanol, ethyl acetate and 1-hexanol) were selected to treat [Mg0.72 Al0.28 (OH)2 ](CO3 )0.14 (Mg2.5 Al-CO3 LDH) and compared with traditional LDH co-precipitated from water. The Brønsted basicity strength of the ST-LDHs and ST-LDOs increased but was accompanied by a decrease in basic site density. In addition, the Lewis acidity of ST-LDOs also changes significantly, with medium strength Lewis acid sites dissapearing after solvent treatment. We found that the CO2 capture capacity of solvent treated LDOs is 50% higher than that of traditional co-precipitated LDO sample. The ethanol treated LDO exhibited the highest CO2 uptake of 1.01 mmol g −1 . The observed CO2 capture performance of the ST-LDOs correlates linearly with the ratio of total acid sites to total basic sites.